Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025DO - 10.58709/niujss.v11i3.2243, 2025)
This edition of NIU Journal of Social Sciences focuses on Godfatherism, Ethnographic Study, Human Security, Entrepreneurship Mentoring Education, Psychological Distress as well as Effective Mental Health Service Utilization. One of the papers, in this issue, reveals that godsons’ preference for political survival above administration has a detrimental effect on public services and infrastructure. It also disclosed that political parties' financial limitations encourage corruption, erode internal democracy. It suggests therefore that electioneering campaigning funds should come directly from consolidated funds established by federal government; political parties in Edo State should implement transparent and democratic systems in candidate selection to eliminate the power of godfathers and the state government and relevant stake holders should develop long-term strategies for sustainable infrastructure development. Another paper also reveals that interventions addressing depression and hopelessness, alongside programmes promoting resilience, social connectedness, and self-worth, are crucial for alleviating distress among unemployed graduates. It therefore, recommends multi-level approaches involving counselling, institutional support, and policy-driven initiatives to enhance psychological well-being and reduce the adverse mental health outcomes associated with graduate unemployment. Readers are advised to make proper use of the ideas presented by the various authors in this issue of NIU Journal of Social Sciences . Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them.